Aquinas on judgment and the active power of reason - Coope, U (2013)
This paper examines Aquinas' account of a certain kind of rational control: The control one exercises in using one's reason to make a judgment. Though this control is not itself a kind of voluntary control, it is a precondition for voluntariness. Aquinas claims that one's voluntary actions must spring from judgments that are subject to one's rational control and that, because of this, only rational animals can act voluntarily. This rational kind of control depends on a certain distinctive feature of the rational faculty. For Aquinas, reason differs from other faculties in that it can be exercised in a peculiarly self-reflective way: In exercising reason one can be grasping the point of what one is doing in that very exercise of reason. The sense in which one controls one's rational judgment is that one is, in judging, guided by the norm of judging truly. Aquinas holds that it is only possible to be so guided because the power by which one judges (namely, reason) is self-reflective in this special sense: part of what it is to judge is to grasp the point of what one is doing in that very act of judging. The paper argues that the roots of this view can be found in neoplatonic discussions of self-constitution and self-knowledge. © 2013 Ursula Coope.